The Effectiveness of the STEM-Based Project Based Learning (PjBL) Learning Model on the Critical Thinking Skills of SPLDV Material of Al-Azhar Paron Middle School Students - Farida Nadzirul Ummah; Budi Sasomo; Arum Dwi Rahmawati (Institute of Educational, Research, and Community Service, 2024)
This study aims to find out whether the STEM-based PjBL learning model is effective on the critical thinking ability of SPLDV material of Al-Azhar Paron Junior High School students. The research used is a quantitative research with a Quasi Experimental design. The population in this study is grade VIII students of Al-Azhar Paron Junior High School. The research sample is the entire population with the number of class VIII A 25 students and class VIII B 21 students. The prerequisite test carried out was a normality test using the Lilliefors formula and a variant homognance test was carried out to see the similarity of variants in both groups. Hypothesis testing is carried out using the unpaired T test. The results of the study showed that the average calculation of the post test results of the experimental class that applied the STEM-based PjBL learning model was higher than that of the control class that applied the conventional learning model. If you look at the results of the unpaired t-test, it shows that the t-count (3.601) is greater than the t-table (2.015) at a significance level of 5%, meaning that the null hypothesis is rejected so that it gives us confidence that the research hypothesis is accepted. These results can then be interpreted that the application of the STEM-based PjBL learning model is effective on the critical thinking skills of SPLDV material of Al-Azhar Paron Junior High School students